Regulatory mechanisms and metabolic changes of miRNA during leaf color change in the bud mutation branches of Acer pictum subsp. mono - Lin, Baoli; Ma, He; Zhang, Kezhong; Cui, Jinteng (Frontiers in Plant Science, 2023)
Acer pictum subsp. mono is a colorful tree species with considerable ornamental and economic value. However, little is known about the metabolism and regulatory mechanism of leaf color change in A. p. subsp. mono. To reveal the molecular mechanism of leaf color change in A. p. subsp. mono, the present study examined the bud mutation branches and compared the metabolites of the red leaves (AR) of the bud mutation branches of A. p. subsp. mono with those of the green leaves (AG) of the wild-type branches. It was found that the chlorophyll and carotenoids content of the red leaves decreased significantly, while anthocyanins, and various antioxidant enzymes increased significantly compared with the green leaves. The glycosides cyanidin, pelargonidin, malvidin, petunidin, delphinidin, and peonidin were detected in AR by liquid chromatography-mass spectrometry. The cyanidin glycosides increased, and cyanidin 3-O-glycoside was significantly upregulated. We analyzed the transcriptome and small RNA of A. p. subsp. mono leaves and detected 4061 differentially expressed mRNAs and 116 differentially expressed miRNAs. Through miRNA-mRNA association analysis, five differentially expressed modules were found; one miRNA targeted three genes, and four miRNAs targeted a single gene. Among them, miR160b, miR6300, and miR396g were found to be the key miRNAs regulating stable anthocyanin accumulation in A. p. subsp. mono leaves. By revealing the physiological response of leaf color change and the molecular regulatory mechanism of the miRNA, this study provides new insight into the molecular regulatory mechanism of leaf color change, thereby offering a foundation for future studies.